A retrospective cohort study of the association between smoking and mortality after acute ST-segment elevation myocardial infarction. Issue 1102 (2nd March 2017) - Steele, Lloyd; Lloyd, Amelia; Fotheringham, James; Sultan, Ayyaz; Iqbal, Javaid; Grech, Ever D
ABSTRACT: Background: Several studies have shown a 'smoker's paradox', where following an acute myocardial infarction, smokers have a paradoxically lower mortality than non-smokers. To date, no large study has investigated this paradox in unselected patients with acute ST-segment elevation myocardial infarction (STEMI) managed by primary percutaneous coronary intervention (PCI) alone. Objectives: We aimed to examine the association of smoking status and 1-year mortality in patients who had STEMI managed by primary PCI. Methods: This retrospective study included all patients admitted with acute STEMI undergoing primary PCI in a single UK centre from January 2009 to April 2012. The survival status for all patients post-STEMI was obtained. Differences in survival by smoking status were assessed using a Kaplan-Meier curve, and after adjustment for age, gender and additional cardiovascular risk factors using a Cox regression analysis. Results: The 1-year mortality for patients with STEMI was 149/1796 (8.3%). There were 846/1796 (47.1%) current smokers, 476/1796 (26.5%) ex-smokers and 417/1796 (23.2%) never smokers. Current smokers were approximately 10 years younger than ex-smokers and never smokers (p=0.001). A multivariate Cox proportional hazards model found no evidence of an association between mortality and smoking status after adjustment; p=0.23. Compared with never smokers, the HR (95% CI) for 1-year mortality for current smokers was 1.47 (0.90 to 2.39) and 1.08 (0.66 to 1.77) for ex-smokers. Conclusions: In this retrospective cohort study, we found no evidence of an association between mortality and smoking status in patients with acute STEMI treated with PCI, and thus no evidence of a 'smoker's paradox'.